The Impact of Financial Reporting Quality on Debt Contracting: Evidence from Internal Control Weakness Reports - COSTELLO, ANNA M.; WITTENBERG‐MOERMAN*, REGINA (Journal of Accounting Research, 2011)
ABSTRACT We examine the effect of financial reporting quality on the trade‐off between monitoring mechanisms used by lenders. We rely on Sarbanes‐Oxley internal control reports to measure financial reporting quality. We find that when a firm experiences a material internal control weakness, lenders decrease their use of financial covenants and financial‐ratio‐based performance pricing provisions and substitute them with alternatives, such as price and security protections and credit‐rating‐based performance pricing provisions. We also find that changes in debt contract design following internal control weaknesses are substantially different from those following restatements, where lenders impose tighter monitoring on managers’ actions, but do not decrease their use of financial statement numbers.